2016
DOI: 10.1534/g3.116.029900
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Interactors of a Mitotic Gene TAO3 Revealed by Functional Analysis of its Rare Variant

Abstract: Studying the molecular consequences of rare genetic variants has the potential to identify novel and hitherto uncharacterized pathways causally contributing to phenotypic variation. Here, we characterize the functional consequences of a rare coding variant of TAO3, previously reported to contribute significantly to sporulation efficiency variation in Saccharomyces cerevisiae. During mitosis, the common TAO3 allele interacts with CBK1—a conserved NDR kinase. Both TAO3 and CBK1 are components of the RAM signalin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…However, when the CDC14 ortholog was knocked out in A. nidulans (Son and Osmani, 2009 ), there was no distinct defect in growth rate. Given that appropriate cell cycle regulation is important for fungal development in yeast and other filamentous fungi, we speculated that the deletion of AflCDC14 may affect cytokinesis in vegetative hyphae, which is consistent with the phenotype defects of septum and down-regulation of septum formation related genes CDC15 (Fankhauser and Simanis, 1993 ) and TAO3 (Gupta et al, 2016 ) in Δ CDC14 mutant. Our study also showed that deletion of AflCDC14 resulted in a severely defective conidia production and morphology (Figure 4 ).…”
Section: Discussionsupporting
confidence: 69%
“…However, when the CDC14 ortholog was knocked out in A. nidulans (Son and Osmani, 2009 ), there was no distinct defect in growth rate. Given that appropriate cell cycle regulation is important for fungal development in yeast and other filamentous fungi, we speculated that the deletion of AflCDC14 may affect cytokinesis in vegetative hyphae, which is consistent with the phenotype defects of septum and down-regulation of septum formation related genes CDC15 (Fankhauser and Simanis, 1993 ) and TAO3 (Gupta et al, 2016 ) in Δ CDC14 mutant. Our study also showed that deletion of AflCDC14 resulted in a severely defective conidia production and morphology (Figure 4 ).…”
Section: Discussionsupporting
confidence: 69%
“…For RME1 , which encodes a negative regulator of the meiotic transcriptional program, an adenine deletion at position -308 upstream of the START codon ( rme1-(del308A) ) results in higher gene expression that leads to inhibition of the meiosis process [Bushkin, Pincus, Morgan, Richardson, Lewis, Chan, Bartel, and Fink 2019; Deutschbauer and Davis 2005]. In the case of TAO3 , which encodes a member of the RAM cell morphogenesis network, a non-synonymous SNP at nucleotide 4477 causes a glutamine to glutamic acid substitution at amino acid 1493 ( tao3-1493QE ), resulting in deregulation of a transcription network important for entry into sporulation [Deutschbauer and Davis 2005; Gupta, Radhakrishnan, Nitin, Raharja-Liu, Lin, Steinmetz, Gagneur, and Sinha 2016]. Finally, a loss-of-function SNP at nucleotide 89 of MKT1 causes a glycine to aspartate change at amino acid 30 ( mkt1-30D ), impacting a transcription network that regulates the early phases of sporulation [Gupta, Radhakrishnan, Raharja-Liu, Lin, Steinmetz, Gagneur, and Sinha 2015; Deutschbauer and Davis 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Sporulation efficiency, the percentage of cells sporulating in a culture in yeast, is a quantitative trait 2026 and is highly heritable across yeast strains. Studies have also highlighted metabolic mediators associated with a single causal SNP in driving sporulation efficiency 27,28 . A previous study 22 has identified four causal quantitative trait nucleotides (QTNs) that confer high sporulation efficiency phenotype, namely, coding variants in sporulation genes IME1 L325M , RSF1 D181G , and non-coding variants in IME1nc A-548 G and RME1 indel-308A .…”
Section: Introductionmentioning
confidence: 99%
“…Sporulation efficiency, the percentage of cells sporulating in a culture in yeast, is a quantitative trait [20][21][22][23][24][25][26] and is highly heritable across yeast strains. Studies have also highlighted metabolic mediators associated with a single causal SNP in driving sporulation efficiency 27,28 .…”
Section: Introductionmentioning
confidence: 99%